Levamisole reduces parasitic infection in juvenile pacu (Piaractus mesopotamicus) - Pahor-Filho, Eduardo [UNESP]; Júnior, Joaber Pereira; Pilarski, Fabiana [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2017)
Anthelmintic drugs are successfully used in aquaculture to control parasitic infections or infestations. This study analyzed the effectiveness of levamisole as an antiparasitic and its effect on the liver of juvenile pacu (Piaractus mesopotamicus). A total of 300 fish (180 ± 1.27 g; 16 ± 0.4 cm) were fed a diet containing levamisole hydrochloride (LHC) for fifteen days. A control group (T0) and four treatments were tested: T1 (100), T2 (150), T3 (300) and T4 (500) mg kg− 1 LHC in quadruplicate (15 fish per repetition). Four fish per treatment (n = 20) were euthanized by sectioning the spinal cord; the sample was forwarded for parasitological analysis. The gill arches and intestines were removed and preserved in formaldehyde 10% for identification and quantification of the parasites. For evaluation of the liver histology, four fish per treatment (n = 20) were euthanized with benzocaine (100 mg L− 1) for liver removal. In intestines and gills, we identified the parasites Rondonia rondoni (Nematoda, Atractinae) and Anacanthorus penilabiatus (Monogenoidea, Dactylogyridae), respectively. Both were at high prevalence and intensity of infection and infestation, respectively. The 300 mg kg− 1 LHC treatment reduced the infection by R. rondoni but not the infestation by A. penilabiatus. Concentrations of 150 and 300 mg kg− 1 LHC caused moderate liver changes, and no changes were observed in fish treated with 100 mg kg− 1 LHC. The highest concentration of LHC (500 mg kg− 1) induced a high occurrence of sinusoid dilation, blood congestion and leukocyte infiltration in fish liver. Our results indicate that LHC (300 mg kg− 1) was effective in controlling the infection by R. rondoni and caused moderate histological changes in pacu liver.
Keywords: Anthelmintic; Aquaculture; Imidotiazol; Liver histology; Parasites